2015
DOI: 10.1007/s11118-015-9486-1
|View full text |Cite
|
Sign up to set email alerts
|

A Note on the Hyperconvexity of Pseudoconvex Domains Beyond Lipschitz Regularity

Abstract: We show that bounded pseudoconvex domains that are Hölder continuous for all α < 1 are hyperconvex, extending the well-known result by Demailly (Math. Z. 194(4) 1987) beyond Lipschitz regularity.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
9
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 11 publications
(9 citation statements)
references
References 21 publications
0
9
0
Order By: Relevance
“…It is well known that two pseudoconvex domains (or even Stein manifolds) Ω 1 and Ω 2 are biholomorphic if and only if O(Ω 1 ) and O(Ω 2 ), the spaces of holomorphic functions, are isomorphic as C-algebras with unit. This implies that the holomorphic structure of a pseudoconvex domain is uniquely determined by algebraic structure of the space of holomorphic functions on it.…”
Section: Introductionmentioning
confidence: 99%
See 3 more Smart Citations
“…It is well known that two pseudoconvex domains (or even Stein manifolds) Ω 1 and Ω 2 are biholomorphic if and only if O(Ω 1 ) and O(Ω 2 ), the spaces of holomorphic functions, are isomorphic as C-algebras with unit. This implies that the holomorphic structure of a pseudoconvex domain is uniquely determined by algebraic structure of the space of holomorphic functions on it.…”
Section: Introductionmentioning
confidence: 99%
“…Let Ω 1 ⊂ C n and Ω 2 ⊂ C m be bounded hyperconvex domains. Suppose that there is a p > 0, p = 2, 4, 6 · · · , such that (1) there is a linear isometry T : A p (Ω 1 ) → A p (Ω 2 ), and (2) the p-Bergman kernels of Ω 1 and Ω 2 are exhaustive, then m = n and there exists a unique biholomorphic map F : Ω 1 → Ω 2 such that |T φ • F ||J F | 2/p = |φ|, ∀φ ∈ A p (Ω 1 ), where J F is the holomorphic Jacobian of F . If n = 1, the assumption of hyperconvexity can be dropped.…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…Kerzman and Rosay also studied which pseudoconvex domains are hyperconvex. We shall not address this question here (see e.g., the introduction of [5] for an up-to-date account of this question). Carlehed et al [17] showed in 1999 the equivalence between (1) and (4).…”
Section: Introductionmentioning
confidence: 99%